P.107 Traumatic spinal cord injuries among aboriginal and non-aboriginal populations of Saskatchewan: a prospective outcomes study. (5th June 2019) - Ahmed, S; Humphreys, S; Liu, L; Fourney, D
Abstract : Background: People of aboriginal ancestry are more likely to suffer traumatic spinal cord injury (TSCI) compared to other Canadians; however, outcome studies are limited. This study aims to compare aboriginal and non-aboriginal populations with acute TSCI with respect to: pre-injury baseline, injury severity, treatment, outcomes, and length-of-stay characteristics.Methods: This was a retrospective analysis of 159 patients with TSCI prospectively enrolled in the prospective Rick Hansen Spinal Cord Injury Registry (RHSCIR), Saskatoon site between February 13, 2010 and December 17, 2016.Results: Sixty-two patients consented to the full dataset, which includes ethnic background: 21 'aboriginal' (33.9%); 41 'non-aboriginal' (66.1%). Aboriginal patients were younger, had fewer medical comorbidities and had similar severity of neurological injury and similar outcomes compared to non-aboriginal patients. However, the time to discharge to the community was significantly longer (median 104.0 days versus 38.5 days, p=0.021). While 35% of non-aboriginal patients were discharged home from the acute care site, no aboriginal patients were transferred home directly.Conclusions: This study suggests a need for better allocation of resources for transition to the community for First Nations patients with TSCI in Saskatchewan. We plan a further study to assess outcomes from TSCI for First Nations patients across Canada.